A study of the recent chemical evolution of the Large Magellanic Cloud - Palma, Tali.; Clariá Olmedo, Juan José.; Geisler, D.; Ahumada, Andrea. (2021)
Abstract: we present the results of a study of the Large Magellanic Cloud (LMC) chemical evolution during the last 2.2 Gyr. This study is based on Washington photometric observations of LMC's star clusters carried out with the Cerro Tololo Inter-American Observatory (CTIO) 4 m telescope, using the C and T_1 filters. As tracers of the LMC's chemical enrichment we used 83 star clusters, from which 40 clusters are projected onto the bar region, 23 in the inner disc and 20 in the outer disc. More than half of the total sample has not been previously studied. We determine size, reddening, deprojected distance, age and metallicity of the observed star clusters.